Bank size and risk-taking under Basel II - Hendrik Hakenes; Isabel Schnabel (Max Planck Institute for Research on Collective Goods, 2005)
This paper discusses the relationship between bank size and risk-taking under Pillar I of the New Basel Capital Accord. Using a model with imperfect competition and moral hazard, we find that small banks (and hence small borrowers) may profit from the introduction of an internal ratings based (IRB) approach if this approach is applied uniformly across banks. However, the banks right to choose between the standardized and the IRB approaches unambiguously hurts small banks, and pushes them towards higher risk-taking due to fiercer competition. This may even lead to higher aggregate risk in the economy.
Keywords: G21; G28; L11; 330; Basel II; IRB approach; bank competition; capital requirements; SME financing; Bank; Betriebsgröße; Kreditrisiko; Bankrisiko; Unvollkommener Wettbewerb; Eigenkapitalvorschriften; Theorie